2009
DOI: 10.2478/v10001-009-0019-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 50 hz magnetic field of different shape on oxygen metabolism in blood platelets: in vitro studies

Abstract: Objectives: The aim of the study was to assess the influence that the shape of low frequency magnetic field may have on catalase and superoxide dismutase activity, malondialdehyde concentration and free radicals generation in human blood platelets. Materials and methods: The suspension of human blood platelets was exposed for 15 min to 50 Hz magnetic field of different shape, and flux density of 10 mT. Results: The determinations of free radicals, malondialdehyde and catalase showed increased values compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…They reported that a 1 min exposure to the electrical field produced by a pacemaker generating pulses with amplitude of 10 V and pulse width of 1 ms at a frequency of 1.7 Hz significantly increased ADP‐induced aggregation of platelets. Henrykowska et al [2009] showed that a 15 min exposure to a 10 mT magnetic field at a frequency of 50 Hz increased the oxidative stress in platelets. Working on prostaglandin I 2 (PGI 2 ) and thromboxane A 2 (TxA 2 ) secretion in endothelial cells of the human umbilical cord vein, Caprani et al [2008] reported that a 20 µT, 1 Hz electromagnetic field exposure affected the thromboembolic equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that a 1 min exposure to the electrical field produced by a pacemaker generating pulses with amplitude of 10 V and pulse width of 1 ms at a frequency of 1.7 Hz significantly increased ADP‐induced aggregation of platelets. Henrykowska et al [2009] showed that a 15 min exposure to a 10 mT magnetic field at a frequency of 50 Hz increased the oxidative stress in platelets. Working on prostaglandin I 2 (PGI 2 ) and thromboxane A 2 (TxA 2 ) secretion in endothelial cells of the human umbilical cord vein, Caprani et al [2008] reported that a 20 µT, 1 Hz electromagnetic field exposure affected the thromboembolic equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…This has been supported by a number of studies, eg., an increase in the O 2 -in cell line immune cells or in primary immune cells (Simkó et al, 2001;Rollwitz et al, 2004;Lupke et al, 2004;Frahm et al, 2006Frahm et al, , 2010Mannerling et al, 2010;Poniedzialek et al, 2013). Other studies have shown that the ELF-MF enhanced the exogenous oxidative stress by, for example, inactivation of hexokinase and depletion of reduced glutathione in red blood cells (Fiorani et al, 1997), or increased production of reactive oxigen species in blood platelets (Henrykowska et al, 2009). In one study brain cells were isolated from rats that had been exposed to 0.01-mT, 60-Hz MF for 24 h or 48 h (Lai and Singh, 2004).…”
Section: Discussionmentioning
confidence: 99%